Blended Learning, Trend Strategi Pembelajaran Masa Depan - Istiningsih, Siti; Hasbullah, Hasbullah (Universitas Hamzanwadi, 2015)
The objectives of this paper is to describe how the role and how to apply starategy blended learning in mathematics. blended learning strategy is mixing two or more strategies or learning methods to obtain the expected learning outcomes. Blended learning strategy in mathematics learning has three components which are mixed into one form of learning. The components consist of 1) online learning, 2) to-face learning, and 3) self-learning. Appropriate blended learning strategy is used in mathematics to study the future of the development of information and communication technology in Indonesia is very adequate.